The Philosophy Of Dealing With The Place In The Creation Of The Painting - Salih Al-obaydi, Esam Nadhum (Opción, 2019)
Painting has always been considered a form of noble artistic expression. How- ever, from the end of the 60s, it became more rare in exhibition spaces. At the end of the 2017s, the desire arose among artists to create a “generic art”. The technique is no longer at the center of their practice. The artist identifies as such and no longer as sculptor or painter. This generic apprehension of art, no longer limited to a “profession”, is widespread in our days. For example, in schools of Fine Arts students are not required to register in the departments of painting, sculpture or engraving but there is a department “Versatile” visual art, where students are free to choose the most appropriate technique for a giv- en project. Today many artists work on the border between several disciplines and produce a work that combines painting, sculpture, video and installation.